KEBEBASAN PERS DAN SENSOR REPRESIF - Murani, Asnawi (Universitas Prof. Dr. Moestopo (Beragama), 2008)
Press, undeniably, has a very strong power to change the society. The moving force comes from the information it carries. Therefore, both the government and other parties should take it into considerations. In anticipating press abuse, the government applies preventive and repressive censorship as a controlling mechanism. Besides, freedom of expression as a form of freedom of the press starts form the human rights. People have their rights to express their feeling as they tike. However, there should be balanced information that assumes responsibility as stated in the draft of Convention on the Freedom of Information. This leads to create the rules of the game between the press and the government in developing the society.